Development, testing and introduction of new diagnostic tools for tuberculosis - Perkins, Mark (Henry Stewart Talks, 2014)
Tuberculosis: current diagnostics tests, microscopy diagnosis in endemic countries, the important distinction between smear negative and smear positive patients -introduction of DOTS, limitations of DOTS, TB notification in Zambia, HIV and TB, Drug resistant TB, TB is a poverty associated disease, The role of FIND in developing new diagnostic tests for TB, Changes in TB testing from 2004 to 2010, Novel testing methods for TB, The role of WHO endorsements for new tests, the Xpert assay, Identification of biomarkers for TB